Lexicalization and language change - Brinton, Laurel J. (Research surveys in linguistics., 2005)
In this up-to-date survey, Laurel Brinton and Elizabeth Traugott examine the various approaches to lexicalization, a process of language change whereby concepts are adopted into the lexicon. Drawing on a number of case studies from the history of English, they then propose a new, unified model of lexicalization and grammaticalization.